2020
DOI: 10.17582/journal.aavs/2021/9.3.416.421
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Antigenic and Molecular Characterization of Sheeppox Virus from Clinical Cases in Egypt

Abstract: Sheep pox is a viral diseases of sheep characterized by fever, generalized papules or nodules, vesicles (rarely), lesions in internal organs and death. Sheeppox virus (SPPV) is the causative agents of Sheeppox, together with goat pox virus (GPV) and lumpy skin disease virus (LSDV) make up the genus Capri poxvirus in the family Poxviridae. The aim of the current study is to monitor and follow up the current situation of Sheeppox (SPPV) in Egypt. A total of thirty-two samples (scabs, biopsies from skin nodules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…3). This result is in agreement with previous investigations that used the specific primers and observed a PCR amplification of 570 bp size (Zhu et al 2013, Hassanien et al 2021, Mikhael and Ali 2022.…”
Section: Resultssupporting
confidence: 93%
“…3). This result is in agreement with previous investigations that used the specific primers and observed a PCR amplification of 570 bp size (Zhu et al 2013, Hassanien et al 2021, Mikhael and Ali 2022.…”
Section: Resultssupporting
confidence: 93%
“…In the present study, four reported isolates of the two Ctenocephalides species of all sexes produced four bands at 570 bp after PCR amplification using oligonucleotide primer sequences targeting the ORF103 gene of Capripoxvirus . Phylogenetic analysis of sheeppox virus revealed that five isolates from sheep collected in China and India 53 , Saudi Arabia, Iraq, and Nigeria 54 , and Egypt 55 , 56 and maintained in the GenBank database were 100% identical. The GPV isolate has been genotyped, described, and confirmed to be 100% inappreciable to a different Egyptian reference strain recovered from goats and registered in GenBank under accession number MW546999 by Mikhael and Ali 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, the disease is endemic [ 11 ]; however, its epidemiological features are not identified. There are commercially available, live attenuated sheeppox vaccines that are being used more for the protection of cattle against lumpy skin disease than for the protection of sheep against sheeppox.…”
Section: Introductionmentioning
confidence: 99%